2011
DOI: 10.5539/gjhs.v4n1p184
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Pattern of Physiological Intracranial Calcifications in a City in Central Africa

Abstract: Objective:Intracranial calcifications underlie certain brain diseases which may be de novo or systemic. But calclfications un-connected to pathologies are classified physiological.Aim:To evaluate physiological intracranial calcifications in Douala with establishment of earliest age range of detection.Materials and Methods:Prospective study of brain computed tomograms was done from April to October 2009 using Schumadzu CT Scan machine. Axial, reconstructed and bone window images as well Hounsfield unit measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…In our study pineal calcification was found as early as 10 years. Uduma et al studied intracranial calcifications in central Africa, 8 highest incidence was found 56% in choroid plexus. They used a single slice scanner with 2 and 5 mm thick sections.…”
Section: Discussionmentioning
confidence: 99%
“…In our study pineal calcification was found as early as 10 years. Uduma et al studied intracranial calcifications in central Africa, 8 highest incidence was found 56% in choroid plexus. They used a single slice scanner with 2 and 5 mm thick sections.…”
Section: Discussionmentioning
confidence: 99%
“…Only in children, the authors seem to agree on the fact that pathology is the most common cause in case of physiological intracranial calcifications. [19,21] However, in past studies with large sample sizes, the frequency of different diseases was only recorded for the group with FCC. Therefore it could not be compared with the FCC-free group.…”
Section: Discussionmentioning
confidence: 99%
“…[8,21,24,26,28,30] The predominance of anterior (and medial) distribution of FCC corresponds to the opinion of most authors. [11,13,17,19,24,29,31] Using 178 FCC on medio-sagittal images of x-ray tomography Lanig [24] calculated a 99% probability that the anterior accumulation of FCC in his sample is not random. In contrast to observations made by Tsitouridis [13] considerably more cases of multiple FCC occurrences in one patient were discovered (about half of all patients examined).…”
Section: Data-discussion-and Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations